The Effect of Extensive Reading on the Students’ Reading Comprehension at the Tenth Grade of SMA Daarul Muttaqien Tangerang in Academic Year 2019/2020 - Nurnazhofah, Euis; Swara, Marrieta Moddies (Foremost Journal, 2020)
Abstract The aim of this research was to know a significant effect of extensive reading on the students' reading comprehension at the tenth grade of SMA Daarul Muttaqien Tangerang. This research used quantitative method, 71 students as the sample which taken by using quasi experimental research and non-equivalent control group design. Students' test and questionnaires were used by the writer to collect the data. The hypothesis data was tested using formula t-test, it was known that in experimental class and control class indicated with Ha was accepted its mean that there was an effect of using extensive reading on the students' reading comprehension at the Tenth grade of SMA Daarul Muttaqien Tangerang, in experimental class the students were focused and had a big spirit in learning reading using extensive reading they were could gave a summary of the reading text with good structure and done the instrument correctly during the learning process. Based on the percentages students' post-test showed that students' reading comprehension was better than before. Moreover, this research also found that students' learning motivation was very good and the students in experimental class were more active in reading using extensive reading during learning process.